Soybean oil, a linoleic acid source, in lamb diets: metabolic, feeding behavior, and ruminal parameters - V. G. O. Lima; L. O. da Silva; J. E. de Freitas Jr.; H. D. R. Alba; V. M. Leite; W. P. Silva; D. D. S. Pina; L. C. Leite; C. S. Rodrigues; S. A. Santos; G. G. P. de Carvalho (Archives Animal Breeding)
​​​​​​​​​​​​​​The objective of this study was to evaluate the effects of including soybean oil (SO) in the diet of feedlot lambs on metabolic, behavioral, and ruminal parameters. Five rumen-cannulated lambs (average body weight of 47.76 ± 7.14 kg at approximately 15 months of age) were distributed in a 5 × 5 Latin square design. Their diets consisted of increasing levels of SO inclusion: 0, 30, 60, 90, and 120 g kg−1 of dry matter (DM). Each period lasted 21 d, with 14 d for adaptation and 7 d for data collection. The data were analyzed using linear and quadratic polynomial contrasts, except for the ruminal fermentation parameters and plasma glucose, which were analyzed using repeated measures over time. There was a linear reduction in DM (P = 0.019) and crude protein (P = 0.007) intake as well as a linear decrease in non-fibrous carbohydrate intake (P < 0.001) and digestibility (P = 0.039) due to increased SO inclusion levels. The intake of ether extract increased linearly (P < 0.001), while its digestibility showed a quadratic relationship (P < 0.001) with the inclusion of SO in the diet. Feeding behavior was not altered by SO inclusion, except for rumination efficiency, which decreased linearly (P < 0.001). There was a linear reduction in nitrogen intake (P = 0.007), while no influence (P > 0.05) of SO inclusion was observed on ruminal fermentation parameters, except for a linear decrease in the concentration of rumen ammonia nitrogen (P = 0.023). The use of SO in diets for feedlot lambs should be approached with caution, as it can reduce DM intake, which may lead to decreased animal performance; however, further studies are needed to determine the effects on the productive cost and performance.